Metafisika dalam Islam: Analisis Komparatif antara Perspektif Filsafat, Ilmu Kalam, dan Tasawuf - Jatim Mistar (STAI Al-Mujtama Pamekasan, 2024)
This study examines the concept of metaphysics within the Islamic intellectual tradition through a comparative analysis of three major disciplines: philosophy, kalam (Islamic theology), and Sufism. Metaphysics, as the study of the nature of being and ultimate reality, holds a central position in Islamic thought but is approached differently across these traditions. Islamic philosophy tends to employ a rational approach, emphasizing the concept of wājib al-wujūd (Necessary Existent), kalam focuses on defending the doctrine of tawhid through theological argumentation, while Sufism emphasizes direct experiential knowledge of the Divine reality. Using qualitative methods and conceptual analysis, this study demonstrates that these three approaches are not contradictory but complementary, collectively contributing to a comprehensive understanding of Islamic metaphysics. The research enriches the discourse of Islamic philosophy by proposing an integrative model that connects reason, revelation, and spiritual experience.